Diagnostic accuracy of SARS-CoV-2 saliva antigen testing in a real-life clinical setting. (June 2022) - Jegerlehner, Sabrina; Suter-Riniker, Franziska; Jent, Philipp; Bittel, Pascal; Nagler, Michael
Highlights: SARS-CoV-2 saliva antigen tests facilitate testing with poorly trained personnel Their diagnostic accuracy in clinical settings is essentially unclear We conducted a diagnostic accuracy study in a real-life clinical setting The diagnostic accuracy of the PCL saliva antigen test was 30.2% Application of the test might lead to a large number of false-negative test results Abstract: Background: SARS-CoV-2 antigen tests with saliva facilitate examination in settings that lack trained personnel. However, little is known about the diagnostic accuracy in real-life clinical settings. Therefore, we studied the diagnostic accuracy of a saliva antigen test in diagnosing SARS-CoV-2 infection in a primary/secondary care testing facility. Methods: Individuals who presented at a COVID-19 testing facility affiliated with a Swiss university hospital were prospectively recruited (n=377). Saliva specimen was obtained, and the PCL Inc. COVID19 Gold antigen test was conducted in parallel with 2 real-time polymerase chain reaction (RT-PCR) assays from a nasopharyngeal swab. Results: RT-PCR results were positive in 53 individuals, corresponding to a prevalence of 14.1% (missing material in 1 individual). The PCL saliva antigen test was positive in 22 individuals (5.8%) and negative in 354 (93.9%). The sensitivity of the saliva antigen test was 30.2% (95% confidence interval 18.3, 44.3), both overall and in symptomatic individuals. The specificity was 98.1% (96.0, 99.3). Conclusions: The diagnostic accuracy of a SARS-CoV-2 saliva antigen test in a primary/secondary care testing facility was remarkably lower than that reported in the manufacturer's specifications.